Food-grade plastic product for sealing and fresh keeping and preparation method of food-grade plastic product
By using components such as quaternary ammonium modified graphite-like carbon nitride in food-grade plastic products, the problem of insufficient antibacterial performance of traditional plastic products is solved, and better food preservation effect and hygiene and safety are achieved.
Patent Information
- Application Number
- CN202411679342.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional food-grade plastic products for sealing and preserving freshness have poor antibacterial performance, resulting in the easy breeding of bacteria in food during transportation and storage, affecting the freshness and safety of food.
Quaternary ammonium modification is prepared through a complex chemical modification process using a food-grade plastic product containing linear low-density polyethylene resin, quaternary ammonium modified graphite carbon nitride, calcium stearate and dioctyl phthalate. graphite-like carbon nitride enhances its antibacterial and antibacterial properties.
It significantly improves the antibacterial and antibacterial properties of food-grade plastic products for sealed and fresh preservation, prevents bacteria from growing, maintains the freshness and quality of food, extends the shelf life, and ensures food hygiene and safety.
Smart Images

Figure BDA0005147898860000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of food preservation, and in particular to a food-grade plastic product for sealing and preservation and a preparation method thereof. Background Art
[0002] With the improvement of living standards, people have higher and higher requirements for food preservation. As one of the main materials for food sealing and preservation, the performance of food-grade plastic film directly affects the safety, freshness and shelf life of food. However, the antibacterial properties of traditional food-grade plastic products for sealing and preservation are poor, which inevitably breeds various bacteria during transportation and long-term storage of the preserved food, causing the food to spoil and deteriorate, affecting the health of the public, and failing to meet the needs of modern food preservation. Therefore, it is necessary to develop a food-grade plastic film with excellent sealing and preservation properties. Summary of the invention
[0003] In order to overcome the above technical problems, the purpose of the present invention is to provide a sealed and fresh-keeping food-grade plastic product and a preparation method thereof, which solves the problem of poor antibacterial performance of traditional sealed and fresh-keeping food-grade plastic products.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A food-grade plastic product for sealing and preserving freshness, comprising the following components in parts by weight:
[0006] 68-82 parts of linear low-density polyethylene resin, 2.5-8.5 parts of quaternary ammonium modified graphite carbon nitride, 1-3 parts of calcium stearate and 10-16 parts of dioctyl phthalate;
[0007] Wherein, the quaternary ammonium modified graphite carbon nitride is prepared by the following steps:
[0008] Step s1: placing urea in a muffle furnace, calcining at a temperature of 550-590° C. for 4-5 hours, then cooling with the furnace, then washing with nitric acid solution and distilled water 2-3 times in sequence, then placing in a vacuum drying oven, drying at a temperature of 80-85° C. for 2-3 hours to obtain graphite carbon nitride;
[0009] Step s2: adding graphite carbon nitride, polyvinyl pyrrolidone, silver acetate and deionized water into a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, ultrasonically dispersing for 30-40 minutes at an ultrasonic power of 300-350W, then introducing nitrogen protection, stirring and reacting for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adding antiascorbic acid solution dropwise while stirring, controlling the dropping rate to 1-2 drops / s, and continuing to stir and react for 2-3 hours after the dropwise addition is completed. After the reaction is completed, the reaction product is centrifuged, the precipitate is washed with distilled water 2-3 times, and then placed in a vacuum drying oven, and dried for 2-3 hours at a temperature of 60-65°C to obtain silver-loaded graphite carbon nitride;
[0010] Step s3: adding graphene oxide and deionized water to a three-necked flask equipped with a stirrer, a thermometer and an air duct, ultrasonically dispersing for 1-1.5 hours at an ultrasonic power of 300-350 W, then introducing nitrogen protection, then adding silver-loaded graphitic carbon nitride and stirring the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 minutes, then heating to 45-50° C. and continuing to stir the reaction for 2-3 hours, and after the reaction is completed, cooling the reaction product to room temperature, and then freeze-drying to obtain doped modified graphitic carbon nitride;
[0011] Step s4: adding the doped modified graphitic carbon nitride, 3-aminopropyltrimethoxysilane and ethanol solution into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introducing nitrogen protection, stirring the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heating to 80-85°C and continuing to stir the reaction for 15-20 hours, and after the reaction is completed, cooling the reaction product to room temperature, then centrifuging, washing the precipitate with toluene and methanol for 2-3 times in turn, and then placing it in a vacuum drying oven, and drying it at a temperature of 60-65°C for 2-3 hours to obtain siloxane-modified graphitic carbon nitride;
[0012] Step s5: adding siloxane-modified graphitic carbon nitride, formaldehyde solution, formic acid and xylene to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introducing nitrogen protection, stirring the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then heating to 90-100°C and continuing to stir the reaction for 15-20h, cooling the reaction product to room temperature after the reaction, and then centrifuging it, washing the precipitate with methanol for 2-3 times, and then placing it in a vacuum drying oven, and drying it at a temperature of 60-65°C for 2-3h to obtain tertiary amine-modified graphitic carbon nitride;
[0013] Step s6: Add tertiary amine-modified graphitic carbon nitride, monobromododecane and xylene into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then raise the temperature to 55-60°C and continue stirring the reaction for 8-10h. After the reaction is completed, cool the reaction product to room temperature and then centrifuge it. Wash the precipitate with methanol 2-3 times in turn, then place it in a vacuum drying oven and dry it at a temperature of 60-65°C for 2-3h to obtain quaternary ammonium-modified graphitic carbon nitride.
[0014] As a further solution of the present invention: the mass fraction of the nitric acid solution in step s1 is 8-12%.
[0015] As a further solution of the present invention: the usage ratio of the graphite carbon nitride, polyvinyl pyrrolidone, silver acetate, deionized water and ascorbic acid solution in step s2 is 5g: 0.2-0.4g: 0.25-0.75g: 100-120mL: 15-20mL.
[0016] As a further embodiment of the present invention: the molar concentration of the antiascorbic acid solution in step s2 is 0.1-0.2 mol / L.
[0017] As a further solution of the present invention: the usage ratio of the graphene oxide, deionized water and silver-loaded graphitic carbon nitride in step s3 is 0.1-0.7 g: 50-60 mL: 0.5 g.
[0018] As a further solution of the present invention: the dosage ratio of the doped modified graphitic carbon nitride, 3-aminopropyltrimethoxysilane and ethanol solution in step s4 is 3g:6-10mL:40-45mL; the volume fraction of the ethanol solution is 85%.
[0019] As a further solution of the present invention: the usage ratio of the siloxane-modified graphitic carbon nitride, formaldehyde solution, formic acid and xylene in step s5 is 3g:5-8mL:5-8mL:40-50mL.
[0020] As a further solution of the present invention: the mass fraction of the formaldehyde solution in step s5 is 37%.
[0021] As a further solution of the present invention: the usage ratio of the tertiary amine-modified graphitic carbon nitride, monobromododecane and xylene in step s6 is 3 g: 5-7 mL: 30-35 mL.
[0022] As a further solution of the present invention: a method for preparing a food-grade plastic product for sealing and preservation, comprising the following steps:
[0023] Step 1: Weigh 68-82 parts of linear low-density polyethylene resin, 2.5-8.5 parts of quaternary ammonium modified graphite carbon nitride, 1-3 parts of calcium stearate and 10-16 parts of dioctyl phthalate according to weight parts, and set aside;
[0024] Step 2: Add linear low-density polyethylene resin, quaternary ammonium modified graphite carbon nitride, calcium stearate and dioctyl phthalate into a mixer, mix well and add into a twin-screw extruder, then melt-extrude, cool and pelletize, and then blow film to obtain a food-grade plastic product for sealing and preservation.
[0025] Beneficial effects of the present invention:
[0026] The invention discloses a food-grade plastic product for sealing and preservation and a preparation method thereof. The method comprises the following steps: adding linear low-density polyethylene resin, quaternary ammonium-modified graphite-like carbon nitride, calcium stearate and dioctyl phthalate into a mixer, mixing the mixture evenly and then adding the mixture into a twin-screw extruder, then subjecting the mixture to melt extrusion, pelletizing after cooling, and then film blowing to obtain the food-grade plastic product for sealing and preservation. In the preparation method, the quaternary ammonium-modified graphite-like carbon nitride is added into the linear low-density polyethylene resin to obtain the food-grade plastic product for sealing and preservation, so that the food-grade plastic product for sealing and preservation has excellent antibacterial and bacteriostatic properties, thereby preventing bacterial growth. After food is sealed and preserved, due to the excellent sealing performance of the food-grade plastic product for sealing and preservation, the loss and penetration of moisture, oxygen and odor substances in the food are effectively prevented, thereby better maintaining the freshness and quality of the food. Furthermore, under the condition of high antibacterial and bacteriostatic properties, the food hygiene and safety are further guaranteed, the shelf life of the food is extended, and the freshness and taste of the food can be better maintained.
[0027] In the process of preparing a sealed and fresh-keeping food-grade plastic product, a sealed and fresh-keeping food-grade plastic product is first prepared. First, urea is used as a raw material to prepare graphitic carbon nitride (g-C3N4). Graphitic carbon nitride has a photocatalytic effect and can produce extremely strong active oxygen under sunlight. It can oxidize lipids in the cell membrane, damage and leak the cell membrane, and make it lose its activity, thereby disinfecting bacteria. Then, doped nanosilver particles and graphene oxide are coated on its surface to obtain doped modified graphitic carbon nitride. Nanosilver particles also have significant photocatalytic and broad-spectrum antibacterial effects. Graphene oxide has good hydrophilicity and dispersibility, as well as a large contact area, and can be used as an electron acceptor. Under the synergistic effect of the two, the efficiency of the photocatalytic reaction of graphitic carbon nitride can be enhanced, thereby improving its photocatalytic antibacterial effect. Then, 3-aminopropyltrimethoxysilane is used to modify the doped modified graphitic carbon nitride. 3-aminopropyltrimethoxysilane The siloxane on the surface is hydrolyzed to form silanol, which can be dehydrated and condensed to be grafted onto the surface of the doped modified graphitic carbon nitride, thereby improving the dispersibility of the doped modified graphitic carbon nitride, so that it can be evenly distributed in food-grade plastic products for sealing and preservation, and at the same time, amino groups are introduced to obtain siloxane-modified graphitic carbon nitride. Then, based on the Eschweiler-Clark amine methylation reaction, the amino groups on the siloxane-modified graphitic carbon nitride are reductively methylated with formaldehyde and formic acid to obtain tertiary amines, thereby obtaining tertiary amine-modified graphitic carbon nitride. Then, tertiary amine-modified graphitic carbon nitride and monobromododecane are reacted. The tertiary amine group on the tertiary amine-modified graphitic carbon nitride reacts with the bromine atom on the monobromododecane to convert the tertiary amine group into a quaternary ammonium group. The quaternary ammonium group is positively charged and can be adsorbed on the negatively charged bacterial cell membrane and destroy the bacterial cell membrane, causing cell inactivation, thereby obtaining quaternary ammonium-modified graphitic carbon nitride. Therefore, adding quaternary ammonium-modified graphitic carbon nitride to food-grade plastic products for sealing and preservation can significantly improve their antibacterial and antimicrobial properties. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Embodiment 1:
[0030] This embodiment is a method for preparing a food-grade plastic product for sealing and preservation, comprising the following steps:
[0031] Step S1: placing urea in a muffle furnace, calcining at a temperature of 550° C. for 4 hours, then cooling with the furnace, then washing twice with a nitric acid solution with a mass fraction of 8% and distilled water, then placing in a vacuum drying oven, and drying at a temperature of 80° C. for 2 hours to obtain graphite carbon nitride;
[0032] Step S2: 5 g of graphite carbon nitride, 0.2 g of polyvinyl pyrrolidone, 0.25 g of silver acetate and 100 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and ultrasonically dispersed for 30 min under an ultrasonic power of 300 W, and then nitrogen protection is introduced, and the reaction is stirred for 20 min at a temperature of 25° C. and a stirring rate of 300 r / min, and then 15 mL of an ascorbic acid solution with a molar concentration of 0.1 mol / L is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the stirring reaction is continued for 2 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 2 h to obtain silver-loaded graphite carbon nitride;
[0033] Step S3: 0.1 g of graphene oxide and 50 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersed for 1 h under an ultrasonic power of 300 W, and then nitrogen protection was introduced, and then 0.5 g of silver-loaded graphitic carbon nitride was added and stirred for 20 min at a temperature of 25 ° C and a stirring rate of 300 r / min, and then the temperature was raised to 45 ° C and the stirring reaction was continued for 2 h. After the reaction was completed, the reaction product was cooled to room temperature, and then freeze-dried to obtain doped modified graphitic carbon nitride;
[0034] Step S4: 3 g of doped modified graphitic carbon nitride, 6 mL of 3-aminopropyltrimethoxysilane and 40 mL of ethanol solution with a volume fraction of 85% are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture is heated to 80° C. and the stirring reaction is continued for 15 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with toluene and methanol in sequence, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 2 h to obtain siloxane-modified graphitic carbon nitride;
[0035] Step S5: 3 g of siloxane-modified graphitic carbon nitride, 5 mL of formaldehyde solution with a mass fraction of 37%, 5 mL of formic acid and 40 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture is heated to 90° C. and the stirring reaction is continued for 15 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with methanol, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 2 h to obtain tertiary amine-modified graphitic carbon nitride;
[0036] Step S6: 3 g of tertiary amine-modified graphitic carbon nitride, 5 mL of monobromododecane and 30 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture is heated to 55° C. and the stirring reaction is continued for 8 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with methanol twice in sequence, and then placed in a vacuum drying oven and dried at a temperature of 60° C. for 2 h to obtain quaternary ammonium-modified graphitic carbon nitride;
[0037] Step S7: weigh 68 parts of linear low-density polyethylene resin, 2.5 parts of quaternary ammonium-modified graphitic carbon nitride, 1 part of calcium stearate and 10 parts of dioctyl phthalate according to weight parts for later use;
[0038] Step S8: Add linear low-density polyethylene resin, quaternary ammonium modified graphite carbon nitride, calcium stearate and dioctyl phthalate into a mixer, mix well and add into a twin-screw extruder, then melt-extrude, cool and pelletize, and then blow film to obtain a food-grade plastic product for sealing and preservation.
[0039] Embodiment 2:
[0040] This embodiment is a method for preparing a food-grade plastic product for sealing and preservation, comprising the following steps:
[0041] Step S1: placing urea in a muffle furnace, calcining at a temperature of 570° C. for 4.5 hours, then cooling with the furnace, then washing twice with a 10% mass fraction nitric acid solution and distilled water, then placing in a vacuum drying oven, and drying at a temperature of 82° C. for 2.5 hours to obtain graphite carbon nitride;
[0042] Step S2: 5 g of graphite carbon nitride, 0.3 g of polyvinyl pyrrolidone, 0.5 g of silver acetate and 110 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and ultrasonically dispersed for 35 min under an ultrasonic power of 325 W, and then nitrogen protection is introduced, and the reaction is stirred for 25 min at a temperature of 28 ° C and a stirring rate of 350 r / min, and then 18 mL of an ascorbic acid solution with a molar concentration of 0.15 mol / L is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the stirring reaction is continued for 2.5 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed twice with distilled water, and then placed in a vacuum drying oven, and dried at a temperature of 62 ° C for 2.5 h to obtain silver-loaded graphite carbon nitride;
[0043] Step S3: 0.4 g of graphene oxide and 55 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersed for 1.2 h under an ultrasonic power of 325 W, and then nitrogen protection was introduced, and then 0.5 g of silver-loaded graphitic carbon nitride was added and stirred for 25 min at a temperature of 28 ° C and a stirring rate of 350 r / min, and then the temperature was raised to 48 ° C and the stirring reaction was continued for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then freeze-dried to obtain doped modified graphitic carbon nitride;
[0044] Step S4: 3 g of doped modified graphitic carbon nitride, 8 mL of 3-aminopropyltrimethoxysilane and 42 mL of ethanol solution with a volume fraction of 85% are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture is heated to 82° C. and the stirring reaction is continued for 18 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with toluene and methanol in sequence, and then placed in a vacuum drying oven and dried at a temperature of 62° C. for 2.5 h to obtain siloxane-modified graphitic carbon nitride;
[0045] Step S5: 3 g of siloxane-modified graphitic carbon nitride, 7 mL of formaldehyde solution with a mass fraction of 37%, 7 mL of formic acid and 45 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture is heated to 95° C. and stirred for reaction for 18 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with methanol, and then placed in a vacuum drying oven and dried at a temperature of 62° C. for 2.5 h to obtain tertiary amine-modified graphitic carbon nitride;
[0046] Step S6: 3 g of tertiary amine-modified graphitic carbon nitride, 6 mL of monobromododecane and 32 mL of xylene were added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen was introduced for protection. The mixture was stirred at 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to 58° C. and the stirring reaction was continued for 9 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with methanol twice in sequence, and then placed in a vacuum drying oven and dried at 62° C. for 2.5 h to obtain quaternary ammonium-modified graphitic carbon nitride;
[0047] Step S7: weigh 75 parts of linear low-density polyethylene resin, 5.5 parts of quaternary ammonium-modified graphite carbon nitride, 2 parts of calcium stearate and 13 parts of dioctyl phthalate according to weight parts for later use;
[0048] Step S8: Add linear low-density polyethylene resin, quaternary ammonium modified graphite carbon nitride, calcium stearate and dioctyl phthalate into a mixer, mix well and add into a twin-screw extruder, then melt-extrude, cool and pelletize, and then blow film to obtain a food-grade plastic product for sealing and preservation.
[0049] Embodiment 3:
[0050] This embodiment is a method for preparing a food-grade plastic product for sealing and preservation, comprising the following steps:
[0051] Step S1: placing urea in a muffle furnace, calcining at a temperature of 590° C. for 5 hours, then cooling with the furnace, then washing with a 12% mass fraction nitric acid solution and distilled water for 3 times, then placing in a vacuum drying oven, and drying at a temperature of 85° C. for 3 hours to obtain graphite carbon nitride;
[0052] Step S2: 5 g of graphite carbon nitride, 0.4 g of polyvinyl pyrrolidone, 0.75 g of silver acetate and 120 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and ultrasonically dispersed for 40 min under an ultrasonic power of 350 W, and then nitrogen protection is introduced, and the reaction is stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then 20 mL of an ascorbic acid solution with a molar concentration of 0.2 mol / L is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain silver-loaded graphite carbon nitride;
[0053] Step S3: 0.7 g of graphene oxide and 60 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersed for 1.5 h under an ultrasonic power of 300-350 W, and then nitrogen protection is introduced, and then 0.5 g of silver-loaded graphitic carbon nitride is added and stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then the temperature is raised to 50° C. and the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then freeze-dried to obtain doped modified graphitic carbon nitride;
[0054] Step S4: 3 g of doped modified graphitic carbon nitride, 10 mL of 3-aminopropyltrimethoxysilane and 45 mL of ethanol solution with a volume fraction of 85% are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 85° C. and stirred for reaction for 20 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with toluene and methanol in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain siloxane-modified graphitic carbon nitride;
[0055] Step S5: 3 g of siloxane-modified graphitic carbon nitride, 8 mL of formaldehyde solution with a mass fraction of 37%, 8 mL of formic acid and 50 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 100° C. and the stirring reaction is continued for 20 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with methanol 3 times, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain tertiary amine-modified graphitic carbon nitride;
[0056] Step S6: 3 g of tertiary amine-modified graphitic carbon nitride, 7 mL of monobromododecane and 35 mL of xylene are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 60° C. and the stirring reaction is continued for 10 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with methanol three times in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain quaternary ammonium-modified graphitic carbon nitride;
[0057] Step S7: 82 parts of linear low-density polyethylene resin, 8.5 parts of quaternary ammonium-modified graphite carbon nitride, 3 parts of calcium stearate and 16 parts of dioctyl phthalate were weighed according to weight parts and set aside;
[0058] Step S8: Add linear low-density polyethylene resin, quaternary ammonium modified graphite carbon nitride, calcium stearate and dioctyl phthalate into a mixer, mix well and add into a twin-screw extruder, then melt-extrude, cool and pelletize, and then blow film to obtain a food-grade plastic product for sealing and preservation.
[0059] Comparative Example 1:
[0060] This comparative example is a method for preparing a food-grade plastic product for sealing and preservation, comprising the following steps:
[0061] Step S1: weigh 82 parts of linear low-density polyethylene resin, 3 parts of calcium stearate and 16 parts of dioctyl phthalate according to weight parts and set aside;
[0062] Step S2: adding linear low-density polyethylene resin, calcium stearate and dioctyl phthalate into a mixer, adding the mixture into a twin-screw extruder after being mixed evenly, and then melt-extruded, pelletized after cooling, and then blown into a film to obtain a food-grade plastic product for sealing and preservation.
[0063] Comparative Example 2:
[0064] This comparative example is a method for preparing a food-grade plastic product for sealing and preservation, comprising the following steps:
[0065] Step S1: placing urea in a muffle furnace, calcining at a temperature of 590° C. for 5 hours, then cooling with the furnace, then washing with a 12% mass fraction nitric acid solution and distilled water for 3 times, then placing in a vacuum drying oven, and drying at a temperature of 85° C. for 3 hours to obtain graphite carbon nitride;
[0066] Step S2: weigh 82 parts of linear low-density polyethylene resin, 8.5 parts of graphite carbon nitride, 3 parts of calcium stearate and 16 parts of dioctyl phthalate according to weight parts, and set aside;
[0067] Step S3: adding linear low-density polyethylene resin, graphite carbon nitride, calcium stearate and dioctyl phthalate into a mixer, mixing evenly and adding into a twin-screw extruder, followed by melt extrusion, pelletizing after cooling, and then film blowing to obtain a food-grade plastic product for sealing and preservation.
[0068] Comparative Example 3:
[0069] This comparative example is a method for preparing a food-grade plastic product for sealing and preservation, comprising the following steps:
[0070] Step S1: placing urea in a muffle furnace, calcining at a temperature of 590° C. for 5 hours, then cooling with the furnace, then washing with a 12% mass fraction nitric acid solution and distilled water for 3 times, then placing in a vacuum drying oven, and drying at a temperature of 85° C. for 3 hours to obtain graphite carbon nitride;
[0071] Step S2: 5 g of graphite carbon nitride, 0.4 g of polyvinyl pyrrolidone, 0.75 g of silver acetate and 120 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and ultrasonically dispersed for 40 min under an ultrasonic power of 350 W, and then nitrogen protection is introduced, and the reaction is stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then 20 mL of an ascorbic acid solution with a molar concentration of 0.2 mol / L is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain silver-loaded graphite carbon nitride;
[0072] Step S3: 82 parts of linear low-density polyethylene resin, 8.5 parts of silver-loaded graphitic carbon nitride, 3 parts of calcium stearate and 16 parts of dioctyl phthalate were weighed according to weight parts and set aside;
[0073] Step S4: adding linear low-density polyethylene resin, silver-loaded graphitic carbon nitride, calcium stearate and dioctyl phthalate into a mixer, adding the mixture into a twin-screw extruder after being mixed evenly, and then melt-extruded, pelletized after cooling, and then blown into a film to obtain a food-grade plastic product for sealing and preservation.
[0074] Comparative Example 4:
[0075] This comparative example is a method for preparing a food-grade plastic product for sealing and preservation, comprising the following steps:
[0076] Step S1: placing urea in a muffle furnace, calcining at a temperature of 590° C. for 5 hours, then cooling with the furnace, then washing with a 12% mass fraction nitric acid solution and distilled water for 3 times, then placing in a vacuum drying oven, and drying at a temperature of 85° C. for 3 hours to obtain graphite carbon nitride;
[0077] Step S2: 5 g of graphite carbon nitride, 0.4 g of polyvinyl pyrrolidone, 0.75 g of silver acetate and 120 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and ultrasonically dispersed for 40 min under an ultrasonic power of 350 W, and then nitrogen protection is introduced, and the reaction is stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then 20 mL of an ascorbic acid solution with a molar concentration of 0.2 mol / L is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the dropwise addition is completed, the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed 3 times with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain silver-loaded graphite carbon nitride;
[0078] Step S3: 0.7 g of graphene oxide and 60 mL of deionized water are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersed for 1.5 h under an ultrasonic power of 300-350 W, and then nitrogen protection is introduced, and then 0.5 g of silver-loaded graphitic carbon nitride is added and stirred for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min, and then the temperature is raised to 50° C. and the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then freeze-dried to obtain doped modified graphitic carbon nitride;
[0079] Step S4: 3 g of doped modified graphitic carbon nitride, 10 mL of 3-aminopropyltrimethoxysilane and 45 mL of ethanol solution with a volume fraction of 85% are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 85° C. and stirred for reaction for 20 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed three times with toluene and methanol in sequence, and then placed in a vacuum drying oven and dried at a temperature of 65° C. for 3 h to obtain siloxane-modified graphitic carbon nitride;
[0080] Step S5: 82 parts of linear low-density polyethylene resin, 8.5 parts of siloxane-modified graphite carbon nitride, 3 parts of calcium stearate and 16 parts of dioctyl phthalate were weighed according to weight parts and set aside;
[0081] Step S6: Add linear low-density polyethylene resin, siloxane-modified graphite carbon nitride, calcium stearate and dioctyl phthalate into a mixer, mix well and add into a twin-screw extruder, then melt-extrude, cool and pelletize, and then blow film to obtain a food-grade plastic product for sealing and preservation.
[0082] The food-grade plastic products for sealing and preservation of Examples 1-3 and Comparative Examples 1-4 were tested for antibacterial properties using the shaking flask method using Escherichia coli, Staphylococcus aureus and Candida albicans as test strains. The test results are shown in the following table:
[0083]
[0084] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be seen that quaternary ammonium-modified graphitic carbon nitride can significantly improve the antibacterial and antimicrobial properties of food-grade plastic products for sealing and preservation.
[0085] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0086] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A food-grade plastic product for sealing and preservation, characterized in that: It comprises the following components in parts by weight: 68-82 parts of linear low-density polyethylene resin, 2.5-8.5 parts of quaternary ammonium modified graphite carbon nitride, 1-3 parts of calcium stearate and 10-16 parts of dioctyl phthalate; Wherein, the quaternary ammonium modified graphite carbon nitride is prepared by the following steps: Step s1: placing urea in a muffle furnace, calcining at a temperature of 550-590° C. for 4-5 hours, then cooling with the furnace, then washing with nitric acid solution and distilled water 2-3 times in sequence, then placing in a vacuum drying oven, drying at a temperature of 80-85° C. for 2-3 hours to obtain graphite carbon nitride; Step s2: adding graphite carbon nitride, polyvinyl pyrrolidone, silver acetate and deionized water into a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, ultrasonically dispersing for 30-40 minutes at an ultrasonic power of 300-350W, then introducing nitrogen protection, stirring and reacting for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then adding antiascorbic acid solution dropwise while stirring, controlling the dropping rate to 1-2 drops / s, and continuing to stir and react for 2-3 hours after the dropwise addition is completed. After the reaction is completed, the reaction product is centrifuged, the precipitate is washed with distilled water 2-3 times, and then placed in a vacuum drying oven, and dried for 2-3 hours at a temperature of 60-65°C to obtain silver-loaded graphite carbon nitride; Step s3: adding graphene oxide and deionized water to a three-necked flask equipped with a stirrer, a thermometer and an air duct, ultrasonically dispersing for 1-1.5 hours at an ultrasonic power of 300-350 W, then introducing nitrogen protection, then adding silver-loaded graphitic carbon nitride and stirring the reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 minutes, then heating to 45-50° C. and continuing to stir the reaction for 2-3 hours, and after the reaction is completed, cooling the reaction product to room temperature, and then freeze-drying to obtain doped modified graphitic carbon nitride; Step s4: adding the doped modified graphitic carbon nitride, 3-aminopropyltrimethoxysilane and ethanol solution into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introducing nitrogen protection, stirring the reaction for 20-30 minutes at a temperature of 25-30°C and a stirring rate of 300-400r / min, then heating to 80-85°C and continuing to stir the reaction for 15-20 hours, and after the reaction is completed, cooling the reaction product to room temperature, then centrifuging, washing the precipitate with toluene and methanol for 2-3 times in turn, and then placing it in a vacuum drying oven, and drying it at a temperature of 60-65°C for 2-3 hours to obtain siloxane-modified graphitic carbon nitride; Step s5: adding siloxane-modified graphitic carbon nitride, formaldehyde solution, formic acid and xylene to a three-necked flask equipped with a stirrer, a thermometer and an air duct, introducing nitrogen protection, stirring the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then heating to 90-100°C and continuing to stir the reaction for 15-20h, cooling the reaction product to room temperature after the reaction, and then centrifuging it, washing the precipitate with methanol for 2-3 times, and then placing it in a vacuum drying oven, and drying it at a temperature of 60-65°C for 2-3h to obtain tertiary amine-modified graphitic carbon nitride; Step s6: Add tertiary amine-modified graphitic carbon nitride, monobromododecane and xylene into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then raise the temperature to 55-60°C and continue stirring the reaction for 8-10h. After the reaction is completed, cool the reaction product to room temperature and then centrifuge it. Wash the precipitate with methanol 2-3 times in turn, then place it in a vacuum drying oven and dry it at a temperature of 60-65°C for 2-3h to obtain quaternary ammonium-modified graphitic carbon nitride.
2. A food-grade plastic product for sealing and preservation according to claim 1, characterized in that: The mass fraction of the nitric acid solution in step s1 is 8-12%.
3. A food-grade plastic product for sealing and preservation according to claim 1, characterized in that: The usage ratio of the graphite carbon nitride, polyvinyl pyrrolidone, silver acetate, deionized water and ascorbic acid solution in step s2 is 5g: 0.2-0.4g: 0.25-0.75g: 100-120mL: 15-20mL.
4. A food-grade plastic product for sealing and preservation according to claim 1, characterized in that: The molar concentration of the antiascorbic acid solution in step s2 is 0.1-0.2 mol / L.
5. The food-grade plastic product for sealing and preservation according to claim 1, characterized in that: The usage ratio of the graphene oxide, deionized water and silver-supported graphitic carbon nitride in step s3 is 0.1-0.7 g:50-60 mL:0.5 g.
6. The food-grade plastic product for sealing and preservation according to claim 1, characterized in that: The dosage ratio of the doped modified graphitic carbon nitride, 3-aminopropyltrimethoxysilane and ethanol solution in step s4 is 3 g: 6-10 mL: 40-45 mL; the volume fraction of the ethanol solution is 85%.
7. The food-grade plastic product for sealing and preservation according to claim 1, characterized in that: The usage ratio of the siloxane-modified graphitic carbon nitride, formaldehyde solution, formic acid and xylene in step s5 is 3 g: 5-8 mL: 5-8 mL: 40-50 mL.
8. The food-grade plastic product for sealing and preservation according to claim 1, characterized in that: The mass fraction of the formaldehyde solution in step s5 is 37%.
9. The food-grade plastic product for sealing and preservation according to claim 1, characterized in that: The usage ratio of the tertiary amine-modified graphitic carbon nitride, monobromododecane and xylene in step s6 is 3 g: 5-7 mL: 30-35 mL.
10. A method for preparing a sealed and fresh-keeping food-grade plastic product according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1: Weigh 68-82 parts of linear low-density polyethylene resin, 2.5-8.5 parts of quaternary ammonium modified graphite carbon nitride, 1-3 parts of calcium stearate and 10-16 parts of dioctyl phthalate according to weight parts, and set aside; Step 2: Add linear low-density polyethylene resin, quaternary ammonium modified graphite carbon nitride, calcium stearate and dioctyl phthalate into a mixer, mix well and add into a twin-screw extruder, then melt-extrude, cool and pelletize, and then blow film to obtain a food-grade plastic product for sealing and preservation.